Assessing customer perception towards service quality (tangibility, reliability and responsiveness) at Section of Contribution EPF Kuantan / Sheha Ibrahim - Ibrahim, Sheha (Bachelor of Science (Hons.) Statistics, 2015)
The main objective for this study is to examine the relationship between service quality provided by Section of Contribution EPF Kuantan and customer perception. Besides that, this study also aimed to identify which factors in dimension of tangibility, reliability and responsiveness that influence customer perception towards service quality provided by Section of Contribution EPF Kuantan. Next, the other objective of this study is to determine any difference in the customer perception between male and female customers towards service quality provided by Section of Contribution EPF Kuantan. There are three independent variables which are tangibility, reliability and responsiveness were used in measuring service quality while dependent variable is customer perception. Data was collected from a sample of 150 respondents by using simple random sampling. The methods of data analysis used were Descriptive Analysis, Pearson Correlation, Multiple Linear Regression and Independent Sample t-Test. The result shows that all independents variable of service quality have positive relationship and there are significant factors in dimension of tangibility, reliability and responsiveness that influence on customer perception at Section of Contribution EPF Kuantan. The result of independent sample t-test shows that there is significant difference in the customer perception between male and female customers towards service quality provided by Section of Contribution EPF Kuantan